2010
DOI: 10.1007/s10490-010-9246-0
|View full text |Cite
|
Sign up to set email alerts
|

Explaining factors affecting individual innovation: The case of producer group members in Thailand

Abstract: Individual innovation and its antecedent factors, both at the group and individual level, are becoming a topic of increasing interest to entrepreneurs. However, research on this area has not yet proved adequate. This study aims to develop and test a multilevel model of antecedents of group members' innovation. Constructive culture and knowledge management are treated as group-level antecedents. Creativity and self-leadership are treated as individual-level antecedents. Data are collected from 1,526 group membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 64 publications
6
71
0
Order By: Relevance
“…As a result of the study conducted by Curral and Marques-Quinteiro (2009) on the relationships between self-leadership and internal motivation, target orientation and innovative behaviors, it can be stated that the development of the self-leadership skills of the employees is a suitable method to increase the innovative behaviors of the employees in the organization. Additionally, in parallel with the findings of the present study, the research conducted by Diliello and Houghton (2008), in which the relationships between self-leadership and creativity are analyzed within the scope of defense acquisition organizations, and the study conducted by Pratoom and Savatsomboon (2010) on the factors affecting individual innovation have determined that self-leadership is an important factor affecting innovative behaviors. All these findings show that self-leadership behaviors affect the innovative behaviors of employees in a positive direction.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…As a result of the study conducted by Curral and Marques-Quinteiro (2009) on the relationships between self-leadership and internal motivation, target orientation and innovative behaviors, it can be stated that the development of the self-leadership skills of the employees is a suitable method to increase the innovative behaviors of the employees in the organization. Additionally, in parallel with the findings of the present study, the research conducted by Diliello and Houghton (2008), in which the relationships between self-leadership and creativity are analyzed within the scope of defense acquisition organizations, and the study conducted by Pratoom and Savatsomboon (2010) on the factors affecting individual innovation have determined that self-leadership is an important factor affecting innovative behaviors. All these findings show that self-leadership behaviors affect the innovative behaviors of employees in a positive direction.…”
Section: Discussionsupporting
confidence: 72%
“…The individual innovation is seen as the source of the institutional innovation and the competitiveness of the institution. In addition, the innovation is a complicated process affected by many factors from the level of institution to the personal levels (Pratoom & Savatsomboon, 2010). However, the institutional level innovation has been the focus of many researches and the individual level factors of the innovation have been ignored (Oldham & Cummings, 1996).…”
Section: Relationship Between Innovation and Self-leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has similarly shown evidence for the strong positive effect of training and development practices on IWB (e.g. Knol & van Linge, 2009;Pratoom & Savatsomboon, 2012;Zhang & Begley, 2011). Based on these findings, we conclude that training and development will enhance IWB, leading to our second hypothesis:…”
Section: Training and Developmentmentioning
confidence: 86%
“…The HRM practice of "training and development" was found to significantly influence IWB in several studies (e.g. Knol and van Linge, 2009;Pratoom and Savatsomboon, 2012;Zhang and Begley, 2011) and all these studies found a direct positive effect. We also saw that "training and development" is a composite of various activities that aim to develop competence and knowledge within organisations.…”
Section: Iwbmentioning
confidence: 99%